Prevalence of risk factors for cardiovascular disease in HIV-infected patients over time: the Swiss HIV Cohort Study. - Glass, T; Ungsedhapand, C; Wolbers, M; Weber, R; Vernazza, P; Rickenbach, M; Furrer, H; Bernasconi, E; Cavassini, M; Hirschel, B; Battegay, M; Bucher, H (2006)
OBJECTIVE: Metabolic changes caused by antiretroviral therapy (ART) may increase the risk of coronary heart disease (CHD). We evaluated changes in the prevalence of cardiovascular risk factors (CVRFs) and 10-year risk of CHD in a large cohort of HIV-infected individuals. METHODS: All individuals from the Swiss HIV Cohort Study (SHCS) who completed at least one CVRF questionnaire and for whom laboratory data were available for the period February 2000 to February 2006 were included in the analysis. The presence of a risk factor was determined using cut-offs based on the guidelines of the National Cholesterol Education Program (NCEP ATP III), the Joint National Committee on Prevention, Detection, Evaluation, and Treatment of High Blood Pressure (JNC7), the American Diabetes Association, and the Swiss Society for Cardiology. RESULTS: Overall, 8,033 individuals completed at least one CVRF questionnaire. The most common CVRFs in the first completed questionnaire were smoking (57.0%), low high-density lipoprotein (HDL) cholesterol (37.2%), high triglycerides (35.7%), and high blood pressure (26.1%). In total, 2.7 and 13.8% of patients were categorized as being at high (>20%) and moderate (10-20%) 10-year risk for CHD, respectively. Over 6 years the percentage of smokers decreased from 61.4 to 47.6% and the percentage of individuals with total cholesterol >6.2 mmol/L decreased from 21.1 to 12.3%. The prevalence of CVRFs and CHD risk was higher in patients currently on ART than in either pretreated or ART-naive patients. CONCLUSION: During the 6-year observation period, the prevalence of CVRFs remains high in the SHCS. Time trends indicate a decrease in the percentage of smokers and individuals with high cholesterol.